2004
DOI: 10.1562/2004-03-19-ra-119.1
|View full text |Cite
|
Sign up to set email alerts
|

Photophysical Properties of Coumarin-30 Dye in Aprotic and Protic Solvents of Varying Polarities¶

Abstract: Experimental results on various photophysical properties of coumarin-30 (C30) dye, namely, Stokes' shift (Deltanu), fluorescence quantum yield (Phi(f)), fluorescence lifetime (tau(f)), radiative rate constant (k(f)) and nonradiative rate constant (k(nr)), as obtained using absorption and fluorescence measurements have been reported. Though in most of the solvents the properties of C30 show more or less linear correlation with the solvent polarity function, Deltaf = [(epsilon - 1)/(2epsilon + 1) - (n(2) - 1)/(2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
92
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 83 publications
(100 citation statements)
references
References 51 publications
6
92
2
Order By: Relevance
“…Coumarin 30 displays its UV-vis absorption peak at 407 nm, and when excited at 380 nm it emits at 482 nm with a QY of 55.3% in acetonitrile. 76 All samples were prepared in toluene and the optical densities of the samples were kept to similar levels (~0.08-0.1). The emission data were collected from 400 nm to 700 nm.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Coumarin 30 displays its UV-vis absorption peak at 407 nm, and when excited at 380 nm it emits at 482 nm with a QY of 55.3% in acetonitrile. 76 All samples were prepared in toluene and the optical densities of the samples were kept to similar levels (~0.08-0.1). The emission data were collected from 400 nm to 700 nm.…”
Section: Resultsmentioning
confidence: 99%
“…The PLQYs of the CdSe(OLA) and CdSe(BA/OLA) nanocrystals were determined to be 11.2 and 26.9 %, respectively, using Coumarin-30 in acetonitrile (PLQY = 55.3 %) as the standard. 76 An ~27% PLQY is the highest value achieved for single-component, white light-emitting ultrasmall CdSe nanocrystals without any post-synthetic surface modification. 34 It is known that when semiconductor nanocrystals are synthesized in the presence of anionic surfactant, the resulting nanocrystals are metal rich.…”
Section: Fluorescence Lifetime Measurement Of White Light-emitting CDmentioning
confidence: 99%
“…(see Scheme 20.3 for molecular structures), behave quite unusually in solvents with relatively high polarity. Thus, in highly polar solvents, these molecules show a marked reduction in fluorescence quantum yields and lifetimes, and subsequently a sharp increase in their non-radiative decay rate [22,23,36,37,[39][40][41][63][64][65].…”
Section: Effect On the Ict To Tict Conversionmentioning
confidence: 99%
“…In this twisted ICT (TICT) state, total charge separation between the dialkylamino and carbonyl moieties takes place because the system is decoupled with a zero overlap of the orbitals involved in the conjugation of the ICT state (see Scheme 20.4). There are enormous numbers of studies reported in the literature to support the formation of the TICT state in coumarin dyes in high-polarity solvents [22,23,36,37,[39][40][41][63][64][65]. As the TICT state is highly polar in nature, in very high-polarity solvents the TICT state can become lower in energy than the planar ICT state.…”
Section: Effect On the Ict To Tict Conversionmentioning
confidence: 99%
See 1 more Smart Citation